Glutathione increase by the n‐butanoyl glutathione derivative (GSH‐C4) inhibits viral replication and induces a predominant Th1 immune profile in old mice infected with influenza virus. Issue 5 (13th March 2019) - Amatore, Donatella; Celestino, Ignacio; Brundu, Serena; Galluzzi, Luca; Coluccio, Paolo; Checconi, Paola; Magnani, Mauro; Palamara, Anna Teresa; Fraternale, Alessandra; Nencioni, Lucia
Abstract: During aging, glutathione (GSH) content declines and the immune system undergoes a deficiency in the induction of Th1 response. Reduced secretion of Th1 cytokines, which is associated with GSH depletion, could weaken the host defenses against viral infections. We first evaluated the concentration of GSH and cysteine in organs of old mice; then, the effect of the administration of the N‐butanoyl GSH derivative (GSH‐C4) on the response of aged mice infected with influenza A PR8/H1N1 virus was studied through the determination of GSH concentration in organs, lung viral titer, IgA and IgG1/IgG2a production, and Th1/Th2 cytokine profile. Old mice had lower GSH than young mice in organs. Also the gene expression of endoplasmic reticulum (ER) stress markers involved in GSH metabolism and folding of proteins, that is, Nrf2 and PDI, was reduced. Following infection, GSH content remained low and neither infection nor GSH‐C4 treatment affected Nrf2 expression. In contrast, PDI expression was upregulated during infection and appeared counterbalanced by GSH‐C4. Moreover, the treatment with GSH‐C4 increased GSH content in organs, reduced viral replication and induced a predominant Th1 response. In conclusion, GSH‐C4 treatment could be used in the elderly to contrast influenza virus infection by inducing immune response, in particular the Th1 profile.